2020
DOI: 10.1002/hep.31324
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide High‐Mobility Group Box 1 Drives Ischemia‐Reperfusion Injury in Human Liver Transplantation

Abstract: Background and Aims Sterile inflammation is a major clinical concern during ischemia‐reperfusion injury (IRI) triggered by traumatic events, including stroke, myocardial infarction, and solid organ transplantation. Despite high‐mobility group box 1 (HMGB1) clearly being involved in sterile inflammation, its role is controversial because of a paucity of patient‐focused research. Approach and Results Here, we examined the role of HMGB1 oxidation states in human IRI following liver transplantation. Portal blood i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…High mobility group box 1 (HMGB1), which is generally accepted as the archetype of alarmin, has recently been documented in human LT. Indeed, Sosa et al (39) showed that disulfide HMGB1 levels increased concomitantly with I/R tissue lesions. Further studies are needed to assess the possible association of HMGB1 with general consequences of I/R and to refine its role in predicting graft function recovery compared with IL-33.…”
Section: Discussionmentioning
confidence: 99%
“…High mobility group box 1 (HMGB1), which is generally accepted as the archetype of alarmin, has recently been documented in human LT. Indeed, Sosa et al (39) showed that disulfide HMGB1 levels increased concomitantly with I/R tissue lesions. Further studies are needed to assess the possible association of HMGB1 with general consequences of I/R and to refine its role in predicting graft function recovery compared with IL-33.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their stability and specificity in most bodily fluids, HMGB1 provides a high potential to serve as a liquid biopsy tool for some cancers and sterile inflammation ( 18 ). Some researchers performed proteomic analyses to the clinical significance of HMGB1 in serum-purified exosomes from malignant mesothelioma cancer patients and identified it as potential biomarkers in diagnosis and prognosis ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 plays an important role in the process of ischemia–reperfusion after TACE, and its acetylation and release are mainly regulated by four main modes ( 18 ). Firstly, large amounts of hypoxanthine accumulated converted to xanthine during anaerobic respiration after the interruption of blood supply, and the resulting ROS prompt cells to release acetylated HMGB1 ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their expression levels were validated by quantitative real-time polymerase chain reaction (qRT-PCR) in the mouse RIRI model. Moreover, their roles in renal and other solid organ transplantations (liver and lung) were explored (26)(27)(28). Additionally, we conducted gene set enrichment and single-cell analyses for these novel genes.…”
Section: Methodsmentioning
confidence: 99%